Ácido hipúrico como indicador de exposición al tolueno en trabajadores de calzado del distrito de el Porvenir - Trujillo - García Caballero, Vilma Jhovana (2016)
In this paper entitled "hippuric acid as an indicator of exposure to toluene in workers footwear district of El Porvenir-Trujillo" whose objectives are: Quantify hippuric from urine samples acid, compare whether the concentration found in the samples urine is within permissible limits provided by WHO, demonstrated by graphs the relationship between the concentration of hippuric acid with working hours, years working, age groups, protective measures, symptoms and labor section of the worker; we worked with 53 urine samples from workers footwear El Porvenir, who often use special adhesives and are in contact with terokal, which in its chemical composition has substances such as toluene, benzene and other toxic substances. Quantification of hippuric acid in urine samples by the titration method and Weichselbaum Probstein average value was 1.37 g / L, with no significant indicator of exposure to toluene as the reference value in urine, according to Organizavión World Health Organization (WHO) to hippuric acid is up to 1, 4 g / L; however the analysis of each value confronting it to different parameters (age, symptoms, years working, etc.) and through the chi-square test statistically significant relationship between elevated concentrations of hippuric acid and years were found to come toiling became footwear workers. Biochemical analyzes were performed in the laboratory of clinical analysis of the Faculty of Pharmacy and Biochemistry, National University of Trujillo